Transforming Islamic Finance through Maqashid Syari'ah: The Bahtsul Masail Approach - Jamaludin Acmad Kholik; Qomarus Zaman; Asmuliadi Lubis (Fenomena, 2025)
The rapid expansion of Islamic finance has been criticized for prioritizing technical Shari’ah compliance over substantive ethical outcomes, resulting in a significant “Maqāṣid deficit.” While prior studies advocate for integrating Maqāṣid al-Sharīʿah and recognize the procedural value of traditional forums like Baḥth al-Masāʾil (BM), a detailed empirical examination of how BM explicitly applies Maqāṣid principles to modern financial products remains lacking. This study aims to fill this gap by investigating how BM operationalizes Maqāṣid—particularly ḥifẓ al-māl (protection of wealth) and ḥifẓ al-nafs (protection of well-being)—in its deliberations on contemporary Islamic finance. Employing a qualitative descriptive-analytical approach, this research collected primary data through interviews and observations of BM sessions in East Java, supplemented by document analysis of fatwās and scholarly texts. The findings reveal a paradigm shift: BM systematically moves beyond validating contractual forms (shurūṭ) to assessing socio-economic impacts, as evidenced in rulings on excessive murābaḥah penalties, exploitative Fintech P2P models, and adaptive agricultural muḍārabah. By synthesizing textual principles (ʿibārāt) with contextual realities (waqiʿ), BM transforms fiqh into a dynamic tool for ethical oversight. This study concludes that BM offers a replicable, bottom-up model for embedding Maqāṣid into financial governance, addressing the theory-practice divide and promoting substantive socio-economic justice in Islamic finance. Ekspansi cepat keuangan syariah telah dikritik karena lebih mengutamakan kepatuhan teknis Shari’ah dibanding hasil etis substantif, menciptakan “defisit Maqāṣid” yang signifikan. Meskipun studi terdahulu menganjurkan integrasi Maqāṣid al-Sharīʿah dan mengakui nilai prosedural forum tradisional seperti Baḥth al-Masāʾil (BM), pemeriksaan empiris rinci tentang bagaimana BM secara eksplisit menerapkan prinsip Maqāṣid pada produk keuangan modern masih kurang. Penelitian ini bertujuan mengisi celah tersebut dengan menyelidiki bagaimana BM mengoperasionalkan Maqāṣid—khususnya ḥifẓ al-māl (perlindungan harta) dan ḥifẓ al-nafs (perlindungan jiwa)—dalam deliberasinya tentang keuangan syariah kontemporer. Dengan pendekatan kualitatif deskriptif-analitis, penelitian mengumpulkan data primer melalui wawancara dan observasi sidang BM di Jawa Timur, dilengkapi analisis dokumen fatwā dan teks keilmuan. Temuan mengungkap pergeseran paradigma: BM secara sistematis bergerak melampaui validasi bentuk kontrak (shurūṭ) ke penilaian dampak sosio-ekonomi, sebagaimana terbukti dalam putusan mengenai denda murābaḥah berlebihan, model Fintech P2P eksploitatif, dan muḍārabah pertanian adaptif. Dengan mensintesis prinsip tekstual (ʿibārāt) dan realitas kontekstual (waqiʿ), BM mengubah fiqh menjadi alat dinamis untuk pengawasan etis. Studi ini menyimpulkan bahwa BM menawarkan model bottom-up yang dapat direplikasi untuk menanamkan Maqāṣid ke dalam tata kelola keuangan, menjembatani kesenjangan teori-praktek dan mempromosikan keadilan sosio-ekonomi substantif dalam keuangan syariah.